Validation of Borg’s RPE 6-20 Scale in Male Industrial Workers of Shiraz City Based on Heart Rate - Abdol-Reza Rajaee-Fard; Ali Reza Choobineh; Hadi Daneshmandi (Majalah-i ̒ilmī pizishkī-i jundī/shapūr, 2012)
Background and Objective: Subjective assessment is a common method for physical workload estimation. In recent years, assessment of perceived exertion or related symptoms of subjective fatigue during physical work has mostly relied upon psycho-physical measurement techniques. Rating scales are the most commonly used measurement instrument in psychology. Borg’s RPE is a simple tool for measuring physical work intensity. This study was conducted to validate Borg’s RPE 6-20 scale (Borg’s Rating of Perceived Exertion) in male industrial workers of Shiraz city.Subjects and Methods: In this study, 500 healthy male workers employed in Shiraz city industries participated voluntarily (age ranged from 20 to 59 years). Subjects were assessed by ergocycle test according to Astrand protocol for 6 minutes. The participants were asked to rate the Borg’s RPE scale during the test at the end of each minute. Additionally, heart rate was recorded by heart rate monitoring device at the end of each minute. Results: Pearson correlation coefficient (r) indicated a high correlation between RPE and heart rate (r= 0.847). Conclusion: The findings of this study showed a high correlation between RPE and HR and confirmed the results of previous studies. Therefore, it can be concluded that Borg’s RPE 6-20 scale may be used to assess the physical work intensity among healthy Iranian male workers.